1986
DOI: 10.1111/j.1651-2227.1986.tb10292.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Regulates the Haemoglobin Concentration in Male Puberty

Abstract: In a longitudinal study of male puberty 20 boys were examined every three months for at least two years. Haemoglobin concentration was determined and related to changes in serum testosterone concentrations. The data show a steep increase in serum testosterone during puberty (p less than 0.001) followed with a five months delay, by a significant increase in haemoglobin concentration (p less than 0.001). It is concluded that the steep increase in serum testosterone during puberty produces an acute stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
7
19
0
Order By: Relevance
“…Bhanushali et al reported a positive impact of socioeconomic status on the anemic status of young adolescent girls [10]. Socioeconomic status of our medical students did not have any significant association on anemia similar to the reports by Thomsen et al [31] while Chaudhary and Dhage have shown a positive association with anemia [23].…”
Section: Kalyanpur and Udaykumarsupporting
confidence: 77%
See 1 more Smart Citation
“…Bhanushali et al reported a positive impact of socioeconomic status on the anemic status of young adolescent girls [10]. Socioeconomic status of our medical students did not have any significant association on anemia similar to the reports by Thomsen et al [31] while Chaudhary and Dhage have shown a positive association with anemia [23].…”
Section: Kalyanpur and Udaykumarsupporting
confidence: 77%
“…There is a negative association between BMI and anemia among women medicos [31], but the statistical significance was not established. We too observed negative association of BMI to Hb concentration among girls who were overweight and obese, but failed to demonstrate statistical significance.…”
Section: Kalyanpur and Udaykumarmentioning
confidence: 99%
“…The prevalence rates of 16·7 % and 34·0 % in male and female adolescents, respectively, are in line with previous studies conducted in the Kingdom and other Gulf countries, which reported anaemia to be higher among female adolescents (22·4-40·0 %) than in males (12·8-18·4 %) (2,(5)(6)(7)9) . It is suggested that in males the achievement of adult testosterone concentration is associated with an increase in erythropoiesis (21) ; therefore, the lower prevalence of anaemia among pubertal/ adolescent boys can be explained by the physiological rise in Hb concentration caused by sexual maturation as well as by decreasing requirements after completion of the growth spurt (22,23) . This fact is supported in our study by showing the 13-14 year age category being at risk of developing anaemia as compared with older age groups (15 and above years).…”
Section: Discussionmentioning
confidence: 99%
“…From childhood to adulthood, however, there is an increase in these and other indices of erythrocyte number and size. This increase is greater in males than females and is probably due to the combined action of several hormones including testosterone and insulin-like growth factor (IGF-1) that are secreted in increased amounts during adolescence (Anttila et al 1994;Thomsen et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one set of genes might affect erythrocyte numbers before puberty, while another set of genes may be responsible for variation during adulthood. Thomsen et al (1986) found that a steep rise in haemoglobin concentration in pubescent boys took place during a short period in adolescence, soon after an increase in testosterone production. In contrast, Anttila et al (1994) in a study of younger boys, failed to find an association between serum testosterone and haemoglobin levels, but did find an association between serum IGF-1 and haemoglobin.…”
Section: Introductionmentioning
confidence: 99%